Consensus recommendations for echocardiography in adults with congenital heart defects from the International Society of Adult Congenital Heart Disease (ISACHD). (1st December 2018) - Li, Wei; West, Cathy; McGhie, Jackie; van den Bosch, Annemien E.; Babu-Narayan, Sonya V.; Meijboom, Folkert; Mongeon, Francois-Pierre; Khairy, Paul; Kimball, Thomas R.; Beauchesne, Luc M.; Ammash, Naser M.; Veldtman, Gruschen R.; et al.
Abstract: The population of adults with congenital heart disease (ACHD) is increasing constantly due to medical, surgical and interventional successes and the input from advanced cardiovascular imaging. ACHD patients are at continuing risk of residua and sequelae related to their CHD contributing to significant morbidity and mortality. Consequently, lifelong expert surveillance is recommended for most patients. Healthcare providers are still working out how best to achieve this objective, how to train enough experts to provide high quality care, and how to organize the delivery of care. Echocardiography is crucial to clinical surveillance providing a comprehensive assessment of cardiac morphology, physiology, pathophysiology, and function. Thus it contributes significantly to the overall clinical management of ACHD patients. The International Society for Adult Congenital Heart Disease (ISACHD; www.isachd.org ) is the leading organization of professionals worldwide dedicated to the pursuit of excellence in the care of ACHD patients. Recognizing the critical role of imaging in the diagnosis and management of ACHD, ISACHD established a task force to provide guidance on echocardiographic studies and reporting. The rationale is that standardization of echocardiographic imaging and reporting carries the potential to improve the overall quality of these exams around the world and facilitate collaborative multicenter research. The standardized ACHD protocols provided by the ISACHD task force (found in the appendices) include specific recommendations for data acquisition and reporting for each of the major adult congenital heart lesions. These protocols give a comprehensive and structured approach in the evaluation of ACHD patients and help to ensure excellent patient care. Highlights: Due to medical advances including imaging there is a growing population of adults with congenital heart diseases Echocardiography is crucial to proactive clinical surveillance ISACHD; www.isachd.org established a task force to provide this guidance on echocardiographic studies and reporting The standardized echocardiography protocols provide recommendations for acquisition and reporting of specific ACHD lesions